Comparative Analysis of Type 2 Diabetes Mellitus Association Patterns in Primary and Referral Care - Muhtar, Muhammad Solihuddin; Hafidh, Kasyfil Azis; Ningrum, Dina Nur Anggraini; Hsu, Min-Huei (BPJS Kesehatan, 2025)
Understanding differential comorbidity patterns for Type 2 Diabetes Mellitus (T2DM) across healthcare levels is crucial for targeted prevention strategies in tiered systems. In this cross-sectional study, we analyzed 2023 BPJS Kesehatan claims data to examine ICD-10-coded comorbidities associated with T2DM between basic primary care facilities (FKTP) and advanced referral care facilities (FKRTL), using weighted and unweighted odds ratios. Distinct patterns emerged reflecting both appropriate care distribution and coding artifacts. FKRTL showed the highest associations with specialized diagnostic: abnormal glucose tolerance (R73, OR: 41.089), unspecified diabetes (E12, OR: 53.023), and insulin-dependent diabetes (E10, OR: 33.807). FKTP demonstrated unexpected associations with conditions beyond its diagnostic capability, notably pulmonary embolism (I26; OR: 112.912), absent in FKRTL’s top 20, suggesting follow-up coding rather than primary diagnosis. Common diabetic complications appeared in both settings: retinopathy (FKTP: OR 44.145 vs FKRTL: OR 25.980) and polyneuropathy (FKTP: OR 25.807 vs FKRTL: OR 26.482), though FKTP lacks specialized diagnostic equipment. Findings reveal appropriate healthcare distribution where FKRTL handles specialized care, while complex diagnostic codes in FKTP likely reflect monitoring of conditions initially diagnosed at referral facilities. This highlights critical interpretation challenges in administrative claims data across tiered healthcare systems managing Indonesia’s millions of T2DM cases.